THU0101 Tissue metabolite of type i collagen, c1m, and crp predicts structural progression of rheumatoid arthritis. (12th June 2018) - Bay-Jensen, A.C.; Platt, A.; Jenkins, M.; Weinblatt, M.; Byrjalsen, I.; Musa, K.; Genovese, M.C.; Karsdal, M.A.
Abstract : Background: Biomarkers of rheumatoid arthritis (RA) disease activity typically measure inflammation or autoimmunity (e.g. CRP, rheumatoid factor (RF)). Another class of biomarkers are structural proteins of the joint. C1M and C3M, metabolites of type I and III collagen, are such biomarkers. These biomarkers have previously been documented to provide additional value as compared to standard inflammation biomarkers, for prognosis and prediction of response to treatment 1 . Objectives: We investigated the relationship of high serum levels of C1M or C3M to radiographic progression, and benchmarked to CRP levels and RF status, demonstrated to be associated with structural progression 2 . Methods: Placebo treated patients of the OSK123 studies (Ph3 clinical trials testing efficacy of fostamatinib) with baseline serum biomarkers C1M, C3M, CRP and RF were included (nBL =474). Van der Heijde mTSS was calculated at baseline and 24 week (n24 =264). Progression was defined as moderate or rapid (≥0.5 or≥5 mTSS units/y). Patients were divided into subgroups; low, high or very high C1M, C3M and CRP (above/below median and highest quartile), or RF negative, positive and high positive (≥110 U/L) 2 . Difference in clinical parameters were analysed by Mann-Whitney/Chi-squared tests, and multivariate predictive calculations by C lassification A nd R egression T ree analysis including covariates (age, BMI, gender and disease activity assessment scores). Results: High C1M, C3M and CRP levels were significantly associated with measures of disease activity (p<0.05) and patient reported scores (p<0.05). RFpos was also associated with disease active scores (p<0.05). RFpos and CRP (p<0.001), as well as C1M and C3M (p<0.05), were significantly associated with mTSS at baseline. For prognostic measures, there were 2.5 and 4-fold as many rapid progressors in the C1Mhigh and CRPhigh (p<0.05), and in the C1Mveryhigh and CRPveryhigh groups (p<0.001) compared C1Mlow and CRPlow, respectively. C1M and CRP performed similarly in the predictive analysis with AUCs of 0.67 and 0.69 (table 1). The best model involving C1M in predicting rapid progressor included BMI, SJC and HAQ (AUC 0.85), whereas the best model for CRP included CRP, BMI, SJC and HAQ (AUC 0.85). C3M and RF did not provide prognostic value. Conclusions: Of the four markers analysed only C1M and CRP were associated with structural progression. They seem to preform equally well, but reflect two different aspect of disease pathogenesis (tissue turnover vs. inflammation), thus may provide individual, but supplementary, information. These simple measures may be important for enrichment of clinical trials with structural progressors. References: [1] Siebuhr A, et al. Serological identification of fast progressors of structural damage with rheumatoid arthritis. Arthritis Res. Ther2013. [2] Aletaha D, Alasti F, & Smolen JS. Rheumatoid factor determines structural progression of rheumatoid arthritis dependent and independent of disease activity. Ann Rheum Dis2013. Disclosure of Interest: A. Bay-Jensen Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, A. Platt Shareholder of: AstraZeneca, Employee of: AstraZeneca, M. Jenkins Employee of: AstraZeneca, M. Weinblatt: None declared, I. Byrjalsen Employee of: Nordic Bioscience, K. Musa Employee of: Nordic Bioscience, M. Genovese: None declared, M. Karsdal Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience